Modified K-Loop Molar Distalization Archwire for Arch Development - Kohli, Sarvraj Singh; Kohli, Virinder Singh (Orthodontic Journal of Nepal, 2020)
Molar distalization is a non-extraction modality in gaining space to alleviate crowding in the dental units. It is also a widely used modality in Class II correction. Several techniques and appliances have been designed for this purpose. In this article a new loop configuration is proposed which can be fabricated on a continuous archwire alongwith a case report of a 14 year old whose malocclusion was managed with it. The Modified K-Loop Molar Distalization Archwire was found to effective and comfortable for the patient. There was no requirement of additional palatal hardware or miniscrews